Stigmatization as a Barrier to Urologic Care: A Review - Parker Foster; Marie Luebke; Abrahim N. Razzak; Danyon J. Anderson; Jamal Hasoon; Omar Viswanath; Alan D. Kaye; Ivan Urits (Health Psychology Research)
Heavy societal stigma of certain conditions has created an environment where individuals may be hesitant to seek professional care. Urology is a specialized field that focuses on many of these conditions that society has deemed taboo to discuss. In this review, we address barriers that have prevented patients from seeking urologic care in order to better understand and elucidate important concerns within development of the physician-patient relationship. Recognizing these concerns can also assist in public health outreach approaches to motivate patients for seeking urologic care. The scope of this review was limited to three highly prevalent conditions affecting both men and women, including urinary incontinence, erectile dysfunction, and genitourinary syndrome of menopause.